A rare cause for primary amenorrhoea - Kaderthambi Hajamohideen Noorul Ameen; Rakesh Pinninti (Wolters Kluwer Medknow Publications, 2012)
Gonadal (ovarian) dysgenesis with normal chromosomes (46, XX), XX female gonadal dysgenesis (XX-GD) is a rare genetically heterogeneous disorder. In 1951, Perrault reported the association of gonadal dysgenesis and deafness, now referred to as Perrault's syndrome. Perrault syndrome is a rare autosomal recessive condition affecting both females and males; only females have gonadal dysgenesis associated with sensorineural deafness, which is present in both sexes. We present a case of sporadic Perrault syndrome in a 35-year-old female with primary amenorrhea, sensorineural deafness, marfanoid features and normal karyotype. There are very few case reports describing the condition, even lesser reports of association with marfanoid habitus. We report this case for its rarity and add to the spectrum of the disease that remains undetermined.